CanLit and Class(room) Struggle - Fogel, Stan (Studies in Canadian Literature, 2000)
The university, once a site of anti-authoritarianism and resistance to power, has become apathetic, perhaps even reactionary, as a result of the consolidation of capitalist powers under free trade and globalization. The study of Canadian literature, once an oppositional practice to American cultural and economic hegemony, has of late been co-opted by the de facto Americanization that is free trade and university/business incorporation. As Canadian governments, and by extension Canadian universities, redefine themselves in neoliberal terms, CanLit should reassert its oppositional ethos and be taught in ways that question and test the limits of the institution and of educational practices.